Diversidad genética de la colección de germoplasma de Myrciaria dubia “camu-camu” de la E.E.A. el Dorado-INIA empleando marcadores microsatélites - Motta Santillán, Daniel Edgar (2022)
Myrciaria dubia (Kunth) McVaugh "camu-camu" is an Amazonian shrub of the Myrtaceae family, which has a high content of vitamin C "ascorbic acid" in the fruit. This compound has a significant international demand from the pharmacological industries. To evaluate the genetic diversity of this species, 380 genotypes from 43 accessions (8 river basins) were collected and analyzed using six simple sequence repeat (SSR) markers. The isolated DNA was of good quality, as demonstrated by spectrophotometric and electrophoretic analysis. The average value of diversity parameters at the accession level were: Number of different alleles (Na), Effective number of alleles (Ne), Shannon's informative index (I), Observed heterozygosity (Ho), Expected heterozygosity (He), and Fixation index (F) of 5,18; 3,63; 1,325; 0,577; 0,652 and 0,124 respectively. The river basins that presented the highest and lowest genetic diversity parameters were Amazonas - Napo and Putumayo - Tigre, respectively. The AMOVA test revealed high genetic variation within populations (73%) and low between populations (27%). The gene flow between river basins ranged from 16,1 (Nanay - Ucayali) to 1,3 (Putumayo - Tigre). Concerning genetic structure, were identified 12 genetic groups, with a delta of K = ~ 4. Likewise, the DAPC by river basin shows that Curaray, Putumayo, and Napo basins were isolated. In conclusion, these results are crucial for planning and designing strategies for conserving, managing, and improving the ex-situ germplasm bank of Myrciaria dubia "camu-camu" in the Loreto region.